THE BIOCHEMICAL CHANGES OF PACKED RED CELLS DURING PRESERVATION - MITOMI, Yoshitada; SASAKAWA, Shigeru; NONAKA, Tomiko; TOKUNAGA, Eiichi (Journal of the Japan Society of Blood Transfusion, 1978)
Changes of glucose, ATP and 2, 3-DPG contents, and posttransfusion survivals were measured in PRC and whole blood in plastic bags during preservation. Biochemical changes in PRC are a little greater than in whole blood stored in plastic bags, but similar to those in whole blood stored in glass bottles. There seem to be no significant differences in survivals between PRC and whole blood.